Brain perfusion in sepsis - Taccone, Fabio Silvio; Scolletta, Sabino; Franchi, Federico; Donadello, Katia; Oddo, Mauro (Current vascular pharmacology, 2013)
Brain dysfunction is a frequent complication of sepsis, usually defined as "sepsis-associated encephalopathy" (SAE). Its pathophysiology is complex and related to numerous processes and pathways, while the exact mechanisms producing neurological impairment in septic patients remain incompletely elucidated. Alterations of the cerebral blood flow (CBF) may represent a key component for the development of SAE. Reduction of CBF may be caused by cerebral vasoconstriction, either induced by inflammation or hypocapnia. Endothelial dysfunction associated with sepsis leads to impairment of microcirculation and cerebral metabolic uncoupling that may further reduce brain perfusion so that CBF becomes inadequate to satisfy brain cellular needs. The natural autoregulatory mechanisms that protect the brain from reduced/ inadequate CBF can be impaired in septic patients, especially in those with shock or delirium, and this further contributes to cerebral ischemia if blood pressure drops below critical thresholds. Sedative agents alter cerebro-vascular reactivity and may significantly reduce CBF. Although disorders of brain perfusion and alteration of CBF and cerebral autoregulation are frequently observed in humans with sepsis, their exact role in the pathogenesis of SAE remains unknown. Brain perfusion can further become inadequate due to cerebral microcirculatory dysfunction, as evidenced in the experimental setting. Microvascular alterations can be implicated in the development of electrophysiological abnormalities observed during sepsis and contribute to neurological alterations in septic animals. The aim of this review is to provide an update on the pathophysiology of brain perfusion in sepsis, with a particular focus on human clinical investigation and novel tools for CBF monitoring in septic patients.